Near-Infrared Broadband Emission for High Electroluminescence Efficiency by Cr3+/In3+-Doped Germanate Phosphors; European Journal of Inorganic Chemistry; Vol. 28, iss. 2 - Peng Su; Qunyang Zhao; Tianchun Lang; Lingling Peng; Polisadova E. F. Elena Fyodorovna; Qinping Qiang; Bitao Liu; Han Tao (2024, 2024)
Title screen